2006
DOI: 10.1007/s11270-006-2027-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Contamination in Vegetables Grown in Urban and Metal Smelter Contaminated Sites in Australia

Abstract: Dietary exposure to heavy metals, namely cadmium (Cd), lead (Pb), zinc (Zn) and copper (Cu), has been identified as a risk to human health through the consumption of vegetable crops. This study investigates the source and magnitude of heavy metal contamination in soil and vegetable samples at 46 sites across four vegetable growing regions in New South Wales, Australia. The four regions Boolaroo, Port Kembla, Cowra and the Sydney Basin were a mix of commercial and residential vegetable growing areas. The extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
184
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(202 citation statements)
references
References 32 publications
10
184
2
6
Order By: Relevance
“…Although Cd is generally the main target element with phytoextraction, Zn is also an element of environmental concern which should also be c o n s i d e r e d w h e n e v a l u a t i n g t h e e ff i c i e n c y o f phytoextraction with N. caerulescens. Numerous urban sites contaminated with trace metals are above thresholds for Zn in Brussels as other urban areas in the world (Imperato et al 2003;Kachenko and Singh 2006;Li et al 2001). This study has confirmed for the first time in field trials the interest of using NMET populations of N. caerulescens for Zn phytoextraction.…”
Section: Soil Influence On Plant Biomass and Concentrationsmentioning
confidence: 99%
“…Although Cd is generally the main target element with phytoextraction, Zn is also an element of environmental concern which should also be c o n s i d e r e d w h e n e v a l u a t i n g t h e e ff i c i e n c y o f phytoextraction with N. caerulescens. Numerous urban sites contaminated with trace metals are above thresholds for Zn in Brussels as other urban areas in the world (Imperato et al 2003;Kachenko and Singh 2006;Li et al 2001). This study has confirmed for the first time in field trials the interest of using NMET populations of N. caerulescens for Zn phytoextraction.…”
Section: Soil Influence On Plant Biomass and Concentrationsmentioning
confidence: 99%
“…15 Com respeito à sua interpretação, um fator de transferência elevado expõe uma débil retenção dos contaminantes no solo e a capacidade de absorção dos metais pela espécie vegetal analisada. 16 Valores de fatores de transferência para Pb encontram-se na faixa 0,01-0,1 e no caso do Cd entre 1-10. 14 Outros estudos expõem fatores de transferência típicos ou considerados de referência para os metais Pb e Cd menores aos reportados anteriormente, os quais estão nas faixas 0,0-0,9 e 0,0-2,7 respectivamente.…”
Section: Disponibilidade E Absorção De Metais Pelas Plantasunclassified
“…In China, thousands of abandoned or operating metal based ore mines exist on public lands, which have generated around 1 500 000 ha of metal polluted soil and increases at a rate of 46 700 ha y À1 (MEPPRC, 2006). Results from recent studies (Kachenko and Singh, 2006;Zhuang et al, 2009) also demonstrate thatthe food crops grown in metal contaminated soils pose a major health concern. For instance, Li et al (2006) reported that Chinese cabbage and Brassica napus grown in the vicinity of a Chinese Pb/Zn mine had higher levels of heavy metals than the maximum permissible value in food proposed by food regulation.…”
Section: Introductionmentioning
confidence: 96%